2022
DOI: 10.3390/pathogens11020128
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Tuberculosis Research and Development: Progress, Priorities and Funding Opportunities

Abstract: In this article, we highlight technological pediatric TB research advances across the TB care cascade; discuss recently completed or ongoing work in adults and corresponding significant research gaps for children; and offer recommendations and opportunities to increase investments and accelerate pediatric TB R&D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Children < 5 years old are at higher risk of developing ATB and pose an increased risk of severe forms of the disease [ 71 ]. Despite the specificity of IGRA for BCG-vaccinated individuals, this test has not been entirely validated by the CDC for testing in children < 5 years old because fewer studies had been conducted previously, the difficulty in blood collection, and the high rate of indeterminate results [ 72 , 73 ].…”
Section: Screening Tests For Tbimentioning
confidence: 99%
“…Children < 5 years old are at higher risk of developing ATB and pose an increased risk of severe forms of the disease [ 71 ]. Despite the specificity of IGRA for BCG-vaccinated individuals, this test has not been entirely validated by the CDC for testing in children < 5 years old because fewer studies had been conducted previously, the difficulty in blood collection, and the high rate of indeterminate results [ 72 , 73 ].…”
Section: Screening Tests For Tbimentioning
confidence: 99%
“…About 1.1 million children fall ill with TB annually and approximately 230,000 deaths (including those living with HIV) were recorded in 2020 [ 2 , 20 , 33 ]. Studies have shown that reported statistics do not provide a true reflection of the global pediatric TB burden because most often, many cases go undiagnosed or unreported and as such, the global statistics could be much higher [ 6 , 20 , 33 , 34 ].…”
Section: Pediatric Tuberculosismentioning
confidence: 99%
“…About 1.1 million children fall ill with TB annually and approximately 230,000 deaths (including those living with HIV) were recorded in 2020 [ 2 , 20 , 33 ]. Studies have shown that reported statistics do not provide a true reflection of the global pediatric TB burden because most often, many cases go undiagnosed or unreported and as such, the global statistics could be much higher [ 6 , 20 , 33 , 34 ]. It has been observed that most reported pediatric fatalities occur in children who are not receiving any TB treatment, meaning that efforts geared towards identifying groups at risk of infection, effective diagnosis, and appropriate treatment require urgent improvement and implementation to significantly reduce TB mortality in children.…”
Section: Pediatric Tuberculosismentioning
confidence: 99%
“…One of the key messages from numerous WHO, STOP-TB Partnership and other global public health expert advisory groups over the past 2 decades have been that increased investment to accelerate TB research and development and bring new diagnostics, biomarkers, transcriptomic blood gene signatures, therapeutics, and vaccines to clinical practice would bring an end the TB pandemic (Mulenga H et al, 2022;Chaisson & Harrington, 2009;Marais B et al, 2010;Raviglione M et al, 2012;Tiberi S et al, 2018;Vjecha MJ et al, 2018;WHO, 2018;WHO, 2021). Adult and paediatric TB research has always been chronically underfunded and the need for more investments into development of new and more patient friendly transformative diagnostics to cover all causes of RTIs, better treatment regimens, preventive vaccines and more recently call for a more precision and personalized medicine and approach to management of RTIs to effect holistic management outcomes (Kumar K et al, 2021;Lange C et al, 2020;Rao M et al, 2019;Nicolau I et al, 2012;McKenna L et al, 2022;Grundner C, 2018;Gebreselassie N et al 2019).…”
Section: Justification For Priority Blue Skies Research On Tuberculosismentioning
confidence: 99%